Perbandingan Metode Pengolahan Kukus, Rebus, dan Goreng Terhadap Nilai Indeks Glikemik Singkong Sebagai Alternatif Karbohidrat Pengganti Nasi Putih - Arina Nurul Ihsani; Chindy Amir; Conita Afriani (Nindikayla Institute, 2024)
The increasing prevalence of diabetes mellitus in Indonesia has prompted the need for healthier alternative carbohydrate sources with a lower glycemic index (GI) than white rice. Cassava is a local food with potential as an alternative carbohydrate source. However, processing methods such as boiling, steaming, and frying can affect starch structure and blood glucose response, thus impacting the food's glycemic index.Objective:To compare the glycemic index values ​​of steamed, boiled, and fried cassava as an alternative carbohydrate source to replace white rice.Methods:This was an observational analytical study with a cross-sectional design. The sample consisted of 10 healthy adult respondents aged 17–25 years selected using consecutive sampling. Respondents fasted for 10–12 hours prior to the examination. Blood glucose levels were measured using a finger prick test at 0, 15, 30, 45, 60, 90, and 120 minutes after consuming the test foods (fried, steamed, and boiled cassava) equivalent to 50 g of carbohydrates and a reference food containing 50 g of pure glucose. The glycemic index (GI) was calculated based on the ratio of the area under the curve (IAUC) between the test foods and the reference foods.Results:The results showed that the processing method influenced the blood glucose response and glycemic index of cassava. Fried cassava had a glycemic index of 14.63 (low category), steamed cassava 43 (low category), and boiled cassava 83 (high category). Fried cassava had the lowest GI, while boiled cassava had the highest.Conclusion:Processing method influenced the glycemic index of cassava. Frying and steaming methods resulted in lower glycemic index values ​​than boiling. Therefore, the selection of cassava processing methods needs to be considered in efforts to control blood glucose levels.